2013
DOI: 10.1089/ars.2012.4584
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Virally Induced Reactive Oxygen Species in Kaposi's Sarcoma Herpesvirus Tumorigenesis

Abstract: Aims: Kaposi's sarcoma (KS), caused by the Kaposi's sarcoma herpesvirus (KSHV), is an AIDS-associated cancer characterized by angiogenesis and proliferation of spindle cells. Rac1-activated reactive oxygen species (ROS) production has been implicated in KS tumorigenesis. We used an animal model of KSHV-induced Kaposi's sarcomagenesis (mECK36) to study the role of ROS in KS and the efficacy of N-acetyl l-cysteine (NAC) in inhibiting or preventing KS. Results: Signaling by the KSHV early lytic gene viral G prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…U Sheyn et al virus, hepatitis C virus and HIV (Perl and Banki, 2000;Ye et al, 2011;Bottero et al, 2013;Ma et al, 2013). On the other hand, in plants, during tobacco mosaic virus infection, ROS signaling was found to initiate plant defense hypersensitive response (Allan et al, 2001;Yoda et al, 2003;Love et al, 2005).…”
Section: Modulation Of Host Ros Metabolismmentioning
confidence: 99%
“…U Sheyn et al virus, hepatitis C virus and HIV (Perl and Banki, 2000;Ye et al, 2011;Bottero et al, 2013;Ma et al, 2013). On the other hand, in plants, during tobacco mosaic virus infection, ROS signaling was found to initiate plant defense hypersensitive response (Allan et al, 2001;Yoda et al, 2003;Love et al, 2005).…”
Section: Modulation Of Host Ros Metabolismmentioning
confidence: 99%
“…Inhibition of ROS by the antioxidant N-acetylcysteine (NAC) has also been shown to prevent KSHV tumorigenesis (6,8). In a PEL mouse model, NAC-treated animals had an extended life span relative to the control group (6).…”
mentioning
confidence: 99%
“…In a PEL mouse model, NAC-treated animals had an extended life span relative to the control group (6). In addition, NAC reduced the tumor size in an endothelial KS-mouse model by inhibiting the expression of both viral and cellular genes involved in proliferation and angiogenesis (8). In all these studies, the role of ROS has been elucidated only in endothelial or B-cell latency models.…”
mentioning
confidence: 99%
“…In vitro studies conducted by Ye et al showed that AIDS-KS strains demonstrate enhanced susceptibility to oxidative stress as induced by either physiologically relevant levels of hydrogen peroxide [18] or conducted by Li et al who show activation through a drug capable of undergoing redox cycling (doxorubicin) [19]. AIDS-KS cells also show an acute hyperresponsiveness to a pro-inflammatory cytokine that signals by redox-mediated pathways (interleukin 6) [20] and possess an inherent perturbation in their thiol redox status characterized by significantly lower levels of both glutathione (GSH) and the GSH reductase co-factor, nicotinamide adenine dinucleotide phosphate [21].…”
Section: Multivariate Discriminant Analysis Of Redox and Progression mentioning
confidence: 99%
“…The better comprehension about the interrelation of viral and host factors in KS carcinogenesis is necessary for the rational development of interdisciplinary clinical interpretation and effective intervention [1,21,22]. The aim of this study was to determine the redox status in AIDS-KS individuals.…”
Section: Multivariate Discriminant Analysis Of Redox and Progression mentioning
confidence: 99%